World Economic Outlook, April 1985. (World Economic Outlook; World Economic Outlook ;, 1985)
This paper highlights that the performance of the world economy in 1984 turned out to be considerably better than had been expected at the beginning of the year. Output grew robustly in the industrial countries, especially in the United States and Japan; inflation continued to decline; and developing countries saw a noteworthy improvement both in their balance-of-payments position and in their domestic growth performance. Fears that the debt situation might deteriorate did not materialize.